Berkeley parenting self-efficacy scale-second grade version: Reliability-validity studies among Turkish families - UYANIK, GÜLDEN (ELSEVIER SCIENCE BV, 2010)
Self efficacy is defined as beliefs in one's capabilities to organize and execute the courses of action required to manage prospective situations (Bandura, 1997). In this study Berkeley Parenting Self-Efficacy Scale (second grade form) was adapted to Turkish families. General survey model was utilized in this study. The answers for the scale of parents having children attending second grade level of elementary schools were evaluated. 536 parents, whose children attending second grade level of elementary private and state schools in Istanbul, included to this study. Berkeley Parenting Self-Efficacy Scale (Second Grade Version) is developed by Susan Hollaway. The results showed that Berkeley Self-Efficacy Scale (for second grade) was reliable and valid instrument for Turkish families. The factor analyses indicated that the subscale of Attainments to the Child in which there are 10 items regarding the strength of own competency feelings of mothers explain 53,90% of total variance. The factor analyses in the second part of the scale is called Motherhood Strategies in which there are 10 items, the few factors were obtained. These factors explain 52,0% of total variance. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Self-efficacy; turkish families; second grade children; scale; reliability; validity; MOTHERS; PREDICTORS; IMPACT